2019
DOI: 10.1016/j.hpb.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clinically significant portal hypertension on outcomes after partial hepatectomy for hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: CSPH had a negative impact on short- and long-term prognoses for HCC patients undergoing partial hepatectomy. However, CSPH did not affect the prognoses in a subgroup of European HCC patients whose CSPH was diagnosed by the standard surrogate criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…And it was expected to be able to give a chance for better long-term OS and DFS ( 21 ). A meta-analysis and review indicated that portal hypertension had an adverse impact on short- and long-term outcomes for HCC patients undergoing partial hepatectomy ( 22 ). Meanwhile, liver cirrhosis was considered as one of the most important risk factors for surgical outcomes in HCC patients ( 3 , 16 , 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…And it was expected to be able to give a chance for better long-term OS and DFS ( 21 ). A meta-analysis and review indicated that portal hypertension had an adverse impact on short- and long-term outcomes for HCC patients undergoing partial hepatectomy ( 22 ). Meanwhile, liver cirrhosis was considered as one of the most important risk factors for surgical outcomes in HCC patients ( 3 , 16 , 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…[33,34] Recently, a meta-analysis also confirmed that clinical PH could negatively influence both short-term and long-term outcomes of patients with HCC after liver resection. [35] Accordingly, in the present study, we excluded patients with portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…However, portal hypertension is inherently associated with deterioration of liver function, and several studies demonstrated that, once patients are stratified according to liver function, portal hypertension is no more an independent prognostic index [114,115,116,117]. Even if the debate is still ongoing, a recent meta-analysis confirmed that indirect signs of portal hypertension (e.g., thrombocytopenia/splenomegaly) are not associated with a worse prognosis following liver resection for HCC [118]. Roayaie et al showed that patients with a low platelet count had lower survival than patients with a normal platelet count, and that survival curves start diverging late (>2 years) after surgery, independently from postoperative recovery [119,120].…”
Section: Prognostic Role Of Platelets In Patients With Hcc Candidamentioning
confidence: 99%